Reframing water governance praxis: Does reflection on metaphors have a role?. (December 2015) - Ison, Ray; Allan, Catherine; Collins, Kevin
Action for adaptation is needed in the face of anthropogenic climate change. The record of adaptation in the field of freshwater governance is poor to date, as it is apparently constrained by operational frameworks. Analyses based on the Contemporary Theory of Metaphor can reveal underlying, often institutionally reified, operational frameworks. We present a desktop metaphor mapping study of one UK and one Australian water management planning document. This mapping demonstrates the potential of metaphor analysis, with further methodological and praxis development, to support the new ways of thinking and acting that are needed to challenge deeply held social and cultural norms of linear, rather than systemic, causality. We suggest that metaphor has the potential to help practitioners expose and examine reified operational frameworks and practices, and to change those that hinder adaptive and systemic praxis.